Meniscal and Articular Cartilage Predictors of Outcome following Revision ACL Reconstruction: A 6-Year Follow-up Study - Wright, Rick (Orthop J Sports Med, 2020)
OBJECTIVES: Previous work has shown that having a lateral meniscectomy prior to revision ACL surgery, as well as grade 3-4 chondral damage to the trochlea at the time of revision ACL surgery results in poorer outcomes at 2 years. Alternatively, meniscal or articular cartilage (AC) pathology documented at the time of a revision surgery were not found to be significant risk factors for 2-year activity levels. The purpose of this study was to follow this cohort for a longer time period, to determine if either meniscal and/or articular cartilage pathology noted at the time of revision ACL surgery significantly affects a patient’s activity level, sports function, and OA symptoms at 6-year follow-up. METHODS: Revision ACL reconstruction patients were identified and prospectively enrolled between 2006 and 2011. Data collected included baseline demographics, surgical technique and pathology, and a series of validated patient reported outcome instruments (IKDC, KOOS, WOMAC, and Marx activity rating score). Patients were followed up for 6 years and asked to complete the identical set of outcome instruments. Regression analysis was used to control for age, gender, BMI, smoking status, activity level, baseline outcome scores, revision number, time since their last ACL reconstruction, graft choice, and previous and current meniscal and articular cartilage pathology, in order to assess the meniscal and AC pathology risk factors for clinical outcomes 6 years after revision ACL reconstruction. RESULTS: 1234 patients met the inclusion criteria and were successfully enrolled, with 716 (58%) males and a median cohort age of 26 years. The median time since their last ACL reconstruction was 3.4 years. Surgeons noted previous pathology in the medial meniscus (39%), lateral meniscus (20%), and articular surfaces (12%) at the time of revision surgery. Surgeons reported current pathology at the time of revision surgery in the medial meniscus (45%), lateral meniscus (36%), medial femoral condyle (MFC; 43%), lateral femoral condyle (LFC; 29%), medial tibial plateau (MTP; 11%), lateral tibial plateau (LTP; 17%), patella (30%), and trochlea (21%). At 6 years, follow-up was obtained on 77% (949/1234). Previous and current meniscal pathology (both medial and lateral), as well as current AC pathology (in the MFC, LTP, trochlea, and patella) were found to be significant drivers of poorer outcomes at 6 years. The most consistent cartilage-related factors driving outcome in revision patients were either a previous or current repair or excision of the medial meniscus and patellofemoral AC pathology. Six-year Marx activity levels were negatively impacted by having either a repair or an excision of the medial meniscus (odds ratio range =0.58-66; 95% CI=0.38-0.91; p=0.01) or having grade 3-4 patellar chondrosis (OR=0.57; 95% CI= 0.35-0.95; p=0.03). Conversely, 6-year activity levels significantly improved by having either a lateral meniscus repair or excision (OR=1.49-2.22; 95% CI=1.07-4.04; p=0.005). Previous medial or lateral meniscal pathology negatively affected all KOOS subscales except for sports/recreation (p<0.05). Articular pathology significantly impaired KOOS symptoms, sports/recreation and the quality of life subscales (p<0.05). The KOOS sports/recreation subscale was significantly affected by articular cartilage pathology (LTP, patella, trochlea; p<0.03). Lower baseline outcome scores, lower baseline activity level, and being a smoker all significantly increased the odds of reporting poorer clinical outcomes at 6 years. CONCLUSION: Meniscal and articular cartilage pathology was found to have a larger impact at 6 years following revision ACL surgery, as compared to 2-year follow-up. In contrast to 2-year follow-up, incidence of medial meniscal and AC pathology at the time of a patient’s revision surgery were found to significantly diminish a patient’s activity level at 6 years, whereas the incidence of lateral meniscal repair or excision was found to improve a patient’s activity level. Having a previous medial meniscal repair or excision or exhibiting grade 2-4 chondral damage noted at the time of ACL revision reconstruction results in poorer IKDC and KOOS scores and worse WOMAC pain and ADL scores at 6 years following revision surgery.